(untitled) (Computer systems and information technologies, 2021)
The paper presents a developed unified information system that can be used for developing real-world crop systems which will give all needed functions for supporting and carrying out crop life parameters. For defining the main structure of the system was developed information model that consists of 4 layers. These layers presented as a cyber physical system. The physical layer represents the flow of physical processes. Under cyberspace defined 3 layers which describe the flow of information that the system would use. For optimizing communication flow CPS contours were defined. This information system defines a whole set of information flow that should use such types of systems that work with crops in edges of the Internet of Things. The developed prototype showed that this information system works as expected and allows the build IoT CPS system which full of needed features for supporting the life of crops.